The total size of an airline and the quality of its flights - Joep van Montfort; Vincent A.C. van den Berg (Tinbergen Institute, 2017)
We examine the relationship between the total size of an airline and its service quality by analysing over 4.8 million domestic flights within the USA in 2016. The total size of an airline is measured by its total market share, total amount of assets or total number of full-time equivalent employees. Delays are a widely used proxy for service quality and the most common category of airline customer complaints. Numerous regressions have been estimated using arrival delay time and whether a flight arrives on time as dependent variables. The regressors of main interest were the total airline size and the degree of competition on the route and airport. We control for weather, congestion, date, and characteristics of the airport, flight and airplane. The results suggest that the larger the total size of an airline, the smaller its average delay time and delay occurrence. Hence, larger airlines seem to offer a higher quality in terms of delays. We also find that an origin airport with less competition may lead to more delays. Surprisingly, a less competitive route may reduce delays.
Keywords: D22; L13; L93; R40; 330; quality; airlines; travel time; delays; airline size